Gender pay equity in Australia: Where are we now and where are we heading? - Todd, P.; Preston, Alison (National Institute of Labour Studies, 2012)
In this article we consider the current trends in gender pay equity in Australia, identifying the lack of improvement, and indeed the recent deterioration, in the national gender wage ratio. We analyse the gender wage gap by industry, State, and labour force status and consider developments in the regulatory sphere and social context which have the potential to have an impact on gender pay equity. We conclude with a discussion of the future prospects for the gender wage gap.